2013
DOI: 10.3390/rs5115550
|View full text |Cite
|
Sign up to set email alerts
|

Time-Space Variability of Chlorophyll-a and Associated Physical Variables within the Region off Central-Southern Chile

Abstract: Time-space fluctuations of chlorophyll-a (Chl-a) within the region off central-southern Chile (33-42°S), and their association with meteorological-oceanographic conditions, were analyzed using satellite time series data (2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012). The mean distribution of moderate values of Chl-a (~0.5 mg•m −3 ) in the northern section (33-38°S) extended out to ~200 km of the coast whereas they were restricted to a narrower band in the southern section (38-42°S). Mean wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 66 publications
1
18
0
Order By: Relevance
“…Nevertheless, central Chile is characterized by its intricate geometry, with gulfs, bays, islands and peninsulas generating high time-space NPP variability. A NPP spatial pattern was observed by Testa (2017) and found by Morales et al (2013) to coincide with Chl-a distribution. Each upwelling system is therefore considered unique in terms of its productivity.…”
Section: Discussionmentioning
confidence: 85%
“…Nevertheless, central Chile is characterized by its intricate geometry, with gulfs, bays, islands and peninsulas generating high time-space NPP variability. A NPP spatial pattern was observed by Testa (2017) and found by Morales et al (2013) to coincide with Chl-a distribution. Each upwelling system is therefore considered unique in terms of its productivity.…”
Section: Discussionmentioning
confidence: 85%
“…Coastal upwelling and solar radiation promote the generation of an upwelling front in this region. Variations in the coastline orientation, bathymetry, general circulation, and mesoscale activity also influence front and eddy generation [56][57][58]. In the area off Point Lavapié, several cyclonic and surface/subsurface anticyclonic eddies are persistently generated in association with higher levels of eddy kinetic energy, and these features move seaward through the CTZ at a relatively low speed (~1.7 km d −1 ) [15,30,32,59].…”
Section: Study Areamentioning
confidence: 99%
“…Remote sensing techniques have been extensively used for monitoring chl-a in aquatic systems [4,[8][9][10]. The advantages of using remote sensing techniques to monitor chl-a are: (1) the geographical coverage of satellite images, which provide information about the entire aquatic system; (2) remote sensing, which allows us to obtain information from inaccessible places; and (3) historical satellite images, which allow the inference of water quality information from the past records [11].…”
Section: Introductionmentioning
confidence: 99%
“…Several methods for estimating chl-a concentration in different turbid waters (Case 2) with remote sensing have been investigated [4][5][6][7][8][9][10][11][12]. Many studies have suggested that remote spectroscopic measurements from the Moderate Resolution Imaging Spectroradiometer (MODIS) should be used to estimate chl-a concentrations in Case 2 waters through empirical and semi-empirical algorithms [4,15,16].…”
Section: Introductionmentioning
confidence: 99%